Perancangan Model Learning Management System untuk Sekolah - Natalia Limantara; Fredy Jingga (Bina Nusantara University, 2014)
Designing a Learning Management System models are useful for schools to assist in teaching and learning. Learning Management System makes the teachers and students can interact with one another without being limited by space and time. Learning Management System was developed using the agile methodology and using the PHP programming language. Data management in a learning management system is using My SQL. Model application's Learning Management System, created web-based, with the aim to enable teachers and students who become a model user of this application, to access lesson plans and learning materials via the internet wherever they are.